Temperature detection in cutting zone for different forms of chip shapes during machining process. Issue 1 (22nd November 2017) - Anicic, Obrad; Jovic, Srdjan; Tasic, Srdan; Vulovic, Aleksa; Jovanovic, Milivoje
Abstract : Purpose: This study aims to detect the temperature distribution in the cutting zone during the machining process. Furthermore, temperature influence in the cutting zone on the forms of chip shapes during the turning of Steel 30CrNiMo8 was evaluated. It is very important to use optimal machining parameters to get the best production results or for high control of the machining process. Design/methodology/approach: Temperature distribution in the cutting zone during the machining process could affect the forms of chip shapes. Forms of chip shapes could be considered as the most important indicator for the quality of the machining process. Findings: Therefore, in this study, the forms of chip shapes based on the temperature distribution in the cutting zone were examined. Originality/value: It was found that the snarled chip type and the loose chip type have the highest temperature variation during the machining process.